2014
DOI: 10.1007/s00705-014-2132-1
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of New World jatropha mosaic virus

Abstract: Full-length sequences of a bipartite begomovirus were obtained from a plant of Jatropha multifida in Florida showing symptoms of foliar mosaic, distortion and necrosis. Sequences of four clones each of a DNA-A and DNA-B were obtained, which showed very low sequence diversity among themselves. The clones were infectious when biolistically inoculated to J. multifida, Phaseolus vulgaris and Nicotiana tabacum, but not to J. curcas. The DNA-A sequences had less than 89 % pairwise identity scores with the DNA-A of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Only a few years ago, citrus and grapevine were reported to be the first woody plants naturally infected by different geminiviruses (Krenz et al, 2012;Loconsole et al, 2012), followed more recently by J. multifida (Polston et al, 2014). In this work, using NGS and bioinformatics tools, we identified a novel geminivirus in apple trees, thus extending the natural hosts of this important virus family to another economically relevant woody crop.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Only a few years ago, citrus and grapevine were reported to be the first woody plants naturally infected by different geminiviruses (Krenz et al, 2012;Loconsole et al, 2012), followed more recently by J. multifida (Polston et al, 2014). In this work, using NGS and bioinformatics tools, we identified a novel geminivirus in apple trees, thus extending the natural hosts of this important virus family to another economically relevant woody crop.…”
Section: Discussionmentioning
confidence: 95%
“…This conclusion is further supported by the analyses of phylogenetic relationships between AGV and representative geminiviruses, selected to include (i) the type species of each genera of the family Geminiviridae, (ii) other species representative of subgroups proposed in some genera of this family based on phylogenetic, biological and/or epidemiological features (Fauquet et al, 2008;Varsani et al, 2014), (iii) geminivirus species sharing a certain sequence identity with AGV (Table 1), and (iv) unclassified geminiviruses infecting woody plants (Al Rwahnih et al, 2013;Loconsole et al, 2012;Polston et al, 2014). When a phylogenetic tree was reconstructed using the Rep protein encoded by these viruses, AGV was clustered together with other members of the genus Begomovirus (Fig.…”
Section: Genome Organization Of Agv and Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, identification of divergent geminiviruses infecting citrus, grapevine and Jatropha multifida (Al Rwahnih et al, 2013;Krenz et al, 2012;Loconsole et al, 2012;Polston et al, 2014;Poojari et al, 2013) has shown that the host range of geminiviruses is not limited to herbaceous plants. In this study we report the identification and characterization of a novel geminivirus infecting mulberry trees, as an addition to the list of woody plants infected by geminiviruses in nature.…”
Section: Discussionmentioning
confidence: 99%
“…African cassava mosaic virus (syn. Cassava latent virus) from Kenya (Bock et al, 1981) and Jatropha mosaic virus from Florida (Polston et al, 2014) have also been reported on J. multifida. However, no virus on J. integerrima and J. podagrica has been reported hitherto.…”
Section: Introductionmentioning
confidence: 96%